PENGARUH KETELADANAN GURU PAI TERHADAP SIKAP BERBUSANA ISLAMI SISWI KELAS X DI SMA MUHAMMADIYAH 4 PALEMBANG - Laila Rahmi Hasanah; Lailatul Mukjizat; Asiana; Mona Alyaa Sausan; Febriyanti; Kurratul Aini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of Islamic Religious Education teachers' role models, the level of Islamic dress implementation among female students, and to examine the influence of Islamic Religious Education teachers' role models on the Islamic dress attitudes of class X female students at SMA Muhammadiyah 4 Palembang. The research method used is quantitative with a descriptive-associative approach. The research sample consisted of 23 female students determined using a purposive sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed using a simple linear regression test with the help of SPSS 25. The results of the study showed that: (1) The Islamic Religious Education teachers' role models were in the